Gurabilāsa pātashāhī dūjī, arathāta, Janama sākhī, athawā, Jīwana britānta srī Gurū Angada Dewa jī : Pañjābī baitāṃ wica - Santa Siṅgha (SAMP early 20th-century Indian books project ;)
Verse work on the life of Angada Dewa, 1504-1552, 2nd guru of the Sikhs.